1994
DOI: 10.1002/j.1460-2075.1994.tb06524.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of DNA replication via Mos function during meiotic divisions in Xenopus oocytes.

Abstract: Meiosis is characterized by the absence of DNA replication between the two successive divisions. In Xenopus eggs, the ability to replicate DNA develops during meiotic maturation, but is normally suppressed until fertilization. Here we show that development of the DNA‐replicating ability depends on new protein synthesis during meiosis I, and that mere ablation of the endogenous c‐mos product Mos allows maturing oocytes to enter interphase and replicate DNA just after meiosis I. Moreover, we demonstrate that dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
242
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(255 citation statements)
references
References 62 publications
11
242
0
2
Order By: Relevance
“…Histone H1 kinase activity in oocytes and extracts were performed as described previously. 39 In vitro phosphorylation of XLX by Cdc2/Cyclin B was carried out as above using 1 mg of the substrate, recombinant GST-XLXwt, or phosphomutants. Products were analyzed by SDS-PAGE and autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Histone H1 kinase activity in oocytes and extracts were performed as described previously. 39 In vitro phosphorylation of XLX by Cdc2/Cyclin B was carried out as above using 1 mg of the substrate, recombinant GST-XLXwt, or phosphomutants. Products were analyzed by SDS-PAGE and autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the p42 MAPK cascade is important at multiple points during maturation: for the initial activation of Cdc2 triggering the G2-M transition (Sagata et al, 1988;Kosako et al, 1994bKosako et al, , 1996Gotoh et al, 1995;Palmer et al, 1998); for Cdc2 reactivation and the suppression of DNA replication during the transition from meiosis 1 to meiosis 2 (Furuno et al, 1994); and for the maintenance of Article published online ahead of print. Mol.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the p42 MAPK cascade is important at multiple points during maturation: for the initial activation of Cdc2 triggering the G2-M transition (Sagata et al, 1988;Kosako et al, 1994bKosako et al, , 1996Gotoh et al, 1995;Palmer et al, 1998); for Cdc2 reactivation and the suppression of DNA replication during the transition from meiosis 1 to meiosis 2 (Furuno et al, 1994); and for the maintenance of metaphase (cytostatic factor) arrest in mature oocytes and eggs (Sagata et al, 1989;Kosako et al, 1994a;Minshull et al, 1994;Abrieu et al, 1996;Cross and Smythe, 1998). In addition, a second MAPK pathway culminating in the activation of c-Jun NH 2 -terminal kinase/stress-activated protein kinase (JNK/SAPK) has been discovered recently in Xenopus oocytes treated with progesterone or subjected to hyperosmolar stress .…”
Section: Introductionmentioning
confidence: 99%
“…Xecdc2(K33R) has a lysine (K) 33 to arginine (R) substitution that disrupts a part of the highly conserved ATP binding site that is essential for the kinase activity (De Bondt et al 1993), and showed no detectable histone H1 kinase activity in Drosophila embryos (see Experimental procedures). Xecdc2(K33R) expressed in a large amounts reduced the histone H1 kinase activity of Cdc2 in Xenopus oocytes (Furuno et al 1994), probably by depleting cyclins from the endogenous protein. It also failed to rescue the mitotic defects in a Drosophila cdc2 mutant (see below, Fig.…”
Section: Kinase Defective Cdc2 Prevents Endoreplicationmentioning
confidence: 99%
“…The following strains were used, salivary gland-specific Gal4 line (Fuse et al 1994); HS-Gal4 on the third chromosome (a gift from Yuh-Nun Jan); imaginal cell specific Gal4 line P127 (K. Guillemin, V. Budnik, J. Nambu & M. Krasnow, personal communication); HS-e2f on the third chromosome (Asano et al 1996); Dmcdc2 B47 and Dmcdc2 E1-24 (Stern et al 1993). UAS lines were made by transforming the cDNAs of Dmcdc2 (Lehner & O'Farrell 1990), Xecdc2 (Furuno et al 1994) and Dmcyclin A (Takahisa et al 1992) on pUAST (Brand & Perrimon 1993) into y 1 Df(1)67c23 embryos by the standard method (Rubin & Spradling 1982). Larval tissue was immunostained as described (Hayashi 1996).…”
Section: Drosophila Strains and Histologymentioning
confidence: 99%